Understanding teaching assistant self-efficacy in role and in training: its susceptibility to influence - Higgins, Helen J.; Gulliford, Anthea (Taylor and Francis, 2014)
There has been a noted growth in the number of teaching assistants (TAs) in mainstream schools (DfE, 2013a). Research is inconclusive about their efficacy at changing outcomes for children (Alborz et al 2009; Blatchford et al, 2009) and has proposed more training for TAs (Russell et al, 2005). Generic training models have suggested that enhancing self-efficacy in turn improves performance. This exploratory study investigated factors that may influence TAs’ sense of self-efficacy and its susceptibility to influence in training. Following two modes of mode of school-based training by Educational Psychologists (EPs) data were collected from 14 mainstream secondary school TAs using focus groups. A thematic analysis noted themes regarding self-efficacy, aligned with Bandura’s (1977) sources of information, outcome expectations and whole school support and norms. Review of the data is likely to be able to guide potential trainers to coach consult strategies which are self-efficacy supportive and which address contextual factors including the perceived status of TAs in schools.